(untitled) (Prosiding Seminar Nasional Pendidikan Universitas Subang (SENDINUSA), 2022)
This study uses a research design Quasi-experimental design-Nonequivalent-Group Design to determine the effect of Task Based Learning on students’ speaking ability. This research will be conducted at SMK Negeri 1 Subang, in a blended learning situation in January 2022. The sample of this research is the second semester tenth grade students Teknik Permesinan 1 and Teknik Permesinan 2. There are 71 students who will be involved in the research; 36 students in the experimental class and 35 students in the control class. In collecting data, researcher will conduct treatment after the pre-test and the results will be known after the post-test. In the pre-test, students will be asked to explain or describe themselves in front of the class directly with a minimum duration of 3 minutes. Treatment will be carried out after the pre-test, the experimental group will use the Task Based Learning method and the control group will only use conventional teaching methods, to determine the effect of using Task Based learning as well as to find out whether there is a difference between using TBL and not using TBL. Treatment will be carried out online and offline depending on the class situation in four meetings. The experimental class will be given the task of making videos and the control group will not. In the experimental class, the researcher gave a theme and asked students to make a video about the theme and upload it to the class WhatsApp group after the lesson was finished as an assignment. In the post-test, students will be tested directly in class to explain themselves in 3 minutes. The data from the pre-test and post-test results will be analyzed using the independent sample t-test SPSS 2.0. The results of the study are assumed to indicate that the use of Task Based Learning can affect students’ speaking ability.